Introduction of Antosianin Extraction from Telang Flower in Vocation School Student - Agustina Puspitasari, Diah; Fauziyah, Mar’atul; Bambang Poerwadi; Christina Wahyu Kartikowati; Supriyono; Oktavian, Rama; Dewi, Laura alvina; Saputra, Qoiru Ramanda; Taqwa, Abiyyu Nabil; Nengseh, Evi Sulviani (Fakultas Teknik, Universitas Brawijaya, 2026)
The partner in this community service program is SMK Muhammadiyah 1 Kepanjen Malang. The partner needs knowledge about the extraction process and its application in the chemical industry. The extraction process is a separation process that involves solvents. The extraction process has two types different of solid-liquid and liquid-liquid extraction which the extraction process is based on chemical and physical properties. Through this activity, the PKM team of the Chemical Engineering Department FTUB introduced the solid-liquid extraction process to teachers and students of SMK Muhammadiyah 1 Kepanjen Malang. The activity consisted of a discussion of the basic concept of the extraction process and practical laboratory work of the anthocyanin extraction process from butterfly pea flowers. During the activity, the participants were very enthusiastic in participating in the activity. In addition, this program also motivates students to continue their education to a higher level by providing more adequate laboratory facilities.